Design and experimental analysis of a vapor compression heat pump combined with double‐stage forced‐circulation evaporators. Issue 5 (29th August 2018) - Lin, Jingxiang; Qin, Guoliang; Jia, Cheng
Abstract: Thermal distillation systems are widely used in the evaporation concentration industry, and the steam is the heating medium of these systems. However, due to the low density of the steam, the volume of equipment and piping is large. Especially in the mechanical vapor recompression (MVR) systems, high impeller exit line speed often occurs in steam compressors, which will cause compressor blades failure easily. In order to solve this problem, an experimental system called a vapor compression heat pump combined with double‐stage forced‐circulation evaporators (VCHP‐FCE) was developed. The system incorporates the refrigerant, R‐22, which offers an energy recycling benefit. R22 is used as the heat resource and has a higher energy‐carrying ability per unit volume than steam. The advantages relative to traditional thermal distillation system include a smaller device size, compact structure and no need for steam resource. Experimental facilities were established to analyze the thermal parameters and performance of the proposed system. The preheating temperature, which was correlated with the refrigerant's evaporation temperature, was the decisive factor affecting the system. A positive correlation was identified between the system's water production rate and the preheating temperature. Based on the first and second laws of thermodynamics, we analyzed the energy balance and the exergy loss of the system. The proportion of energy loss in each unit and the complete system exergy efficiency as a function of the environmental temperature were determined, which together indicated directions for system improvement. Abstract : A vapor compression heat pump combined with double‐stage forced‐circulation evaporators (VCHP‐FCE), was developed. The system incorporates the most commonly used refrigerant, R‐22, which offers an energy recycling benefit. This refrigerant is used as the heat resource and has a higher energy‐carrying ability per unit volume than steam.